(untitled) (International Journal of Food and Nutritional Sciences, 2023)
A field experiment was conducted during the Rabi season of 2023–24 in Mandhana, Kanpur district, Uttar Pradesh, to evaluate the impact of integrated nutrient management on the growth, yield attributes, and yield of chickpea (Cicerarietinum L.). The soil was characterized as loamy sand with a pH of 7.68, electrical conductivity of 0.24 dSm⁻¹, organic carbon content of 0.45%, and available nitrogen, phosphorus, and potassium levels of 218.25, 20.50, and 157.30 kg ha⁻¹, respectively. The study was arranged in a Randomized Block Design (RBD) with 14 treatment combinations replicated three times. The treatments included varying levels of organic and inorganic nutrient sources. This investigation aimed to identify effective nutrient management practices to enhance chickpea productivity. Results demonstrated significant differences among treatments in terms of growth parameters, yield attributes, and overall yield, emphasizing the importance of integrated nutrient management in improving chickpea performance under the tested agro-climatic conditions.